THE EVALUATION OF RATIONAL USE OF SOME DRUGS IN ALBANIA - Miraci, Mirela; Haloci, Entela; Toto, Benuarda (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The irrational use of medicines is a major problem worldwide. The irrational antibiotics are one of the causes of mortality and morbidity around the world and the increasing of antimicrobial resistance too. The objective is to study the consumption of some reimbursement drugs, the study of consumption of main antibiotics in a few pharmacies in Tirana, Albania and at the same time, to study the knowledge of the random antibiotic use of patients in Tirana. Methods: Part I. There are five pharmacies randomly selected in Tirana, which are part this study. They accepted us to have access to a considerable number (2910) of reimbursement prescriptions, consumed in a total of 5 months. The medical prescriptions were analyzed for: (1) The average total number of drugs prescribed; (2) The percentage of drug prescribed with the right generic name; (3) The percentage of antibiotics prescribed; (4) The percentage of injectable pharmaceutical forms prescribed; (5) The average cost of every reimbursement prescription. Part II. There are taken into consideration ten pharmacies located in the city of Tirana. The consumption and the knowledge of the patients about antibiotics were analyzed. The data are collected for a single month (May 2014). We took into consideration the entries of antibiotics and antimicrobials subtracting the present stock of these drugs. Results: As we see from the results in there are 91.6% of reimbursement prescription prescribed in accordance with low Albanian Drug Regulation. The average number of drugs prescription is about 2 which means we have not overprescribed of drugs in reimbursement ones. The average of the percentage of injectable forms is 3.18, which is not very high too. Azithromycin has the highest consume, followed by amoxicillin, and the chloramphenicol has the lowest one. A high number of patients interviewed (in total 148 or 59.2%) are answered that they take antibiotics only with a medical prescription, and there were not a significant difference between female and males. Conclusions: The findings of this study suggest that the drugs given in reimbursement prescription are generally in accordance with diagnosis and rational prescription. Further investigation is needed to analyze non-reimbursement prescription which do not have the some monitoring system which means that may have more problems that reimbursement ones. The authorities must have under control the enforcement of regulation low for drug purchasing process. On the other hand, we should sensibilize all the age groups to avoid self-medication especially with antibiotics which cause the resistance problems. The doctors should be careful not to prescribe the drugs by trade name respecting the proper protocols. Keywords: Rational use, Reimbursement drugs, Antibiotic